APPLICATION OF INDUCTIVE-DEDUCTIVE APPROACH TO IMPROVE THE ABILITY OF MATHEMATICAL COMMUNICATION AND SELF EFFICACY OF JUNIOR HIGH SCHOOL STUDENT - Bibih Hasibah; Euis Eti Rohaeti; Bambang Aryan ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This study aims to analyze the application of inductive-deductive approach to improve the ability of mathematical communication and self efficacy of junior high school students. The design of this study is quasi experiment. The research instruments used in this research are mathematical communication ability test and self efficacy attitude scale. The population in this study is all students of SMP Negeri 1 Soreang with this research sample is 80 students of class VIII as much as two classes chosen at random. Data analysis was done quantitatively to the data of mathematic communication ability and self efficacy attitude scale. In statistical calculations using SPSS 21, the results of the study show that improving students' mathematical communication skills whose learning uses a deductive-inductive approach is better than using ordinary learning. And self efficacy of junior high school students whose learning using inductive -deductive approach is better than using ordinary learning. Keywords:  Mathematical Communication Skills, Self Efficacy, Deductive-induktive approach